The effects of NCAA Division 1 intercollegiate competitive tennis match play on recovery of physical performance in women - Kraemer, W. J.; Piorkowski, P. A.; Bush, J. A.; Gomez, A. L.; Loebel, C. C.; Volek, J. S.; Newton, R. U.; Mazzetti, S. A.; Etzweiler, S. W.; Putukian, M.; Sebastianelli, W. J. (The Journal of Strength and Conditioning Research, 2000)
The effects of 2 days of Big Ten National Collegiate Athletic Association Division 1 tennis match play were studied in 7 women. The unique design of this study was the first to use an actual collegiate match-play situation incorporating all of the actual stresses involved in the multidimensional game of tennis. Physical strength, power, and several physiological measures were evaluated in an attempt to identify specific variables created by the demands of actual play that may not recover from fatigue. The test battery included determination of peak ball velocity in the serve, peak torque of both internal and external shoulder rotation, maximal grip strength, vertical jumps on the force plate, and salivary cortisol concentrations. Prior to the study, baseline measures for the test battery were established with reliabilities of intraclass correlation coefficients of R 0.95. Each performance variable sufficiently recovered after 24 hours; no significant differences were observed between baseline and the test session 24 hours postmatch. Significant (p < 0.05) correlations were observed between force variables of the dominant playing arm and the performance variable of serve velocity (r = 0.75-0.82). It appears that a 24-hour recovery period will allow a majority of a tennis player's neuromuscular performance characteristics to recover from successive days of collegiate match-play competition; however, mental and physical perceptions of fatigue may still exist.